Pseudomonas aeruginosa LasB Subverts Alveolar Macrophage Activity by Interfering With Bacterial Killing Through Downregulation of Innate Immune Defense, Reactive Oxygen Species Generation, and Complement Activation - Bastaert, Fabien; Kheir, Saadé; Saint-Criq, Vinciane; Villeret, Bérengère; Dang, Pham My-Chan; El-Benna, Jamel; Sirard, Jean-Claude; Voulhoux, Romé; Sallenave, Jean-Michel (Frontiers in Immunology, 2018)
Pseudomonas aeruginosa (P.a) is a pathogen causing significant morbidity and mortality, in particular in hospital patients undergoing ventilation and in patients with cystic fibrosis. Among the virulence factors secreted or injected into host cells, the physiopathological relevance of type II secretions system (T2SS) is less studied. Although there is extensive litterature on the destructive role of LasB in vitro on secreted innate immune components and on some stromal cell receptors, studies on its direct action on myeloid cells are scant. Using a variety of methods, including the use of bacterial mutants, gene-targeted mice and proteomics technology, we show here, using nonopsonic conditions (thus mimicking resting and naïve conditions in the alveolar space), that LasB, an important component of the Pseudomonas aeruginosa T2SS is highly virulent in vivo, and can subvert alveolar macrophage (AM) activity and bacterial killing, in vitro and in vivo by down-regulating important secreted innate immune molecules (complement factors, cytokines…) and receptors (IFNAR, Csf1r…). In particular, we show that LasB down-regulates the production of C3 and factor B complement molecules, as well as the activation of ROS production by AM. In addition, we showed that purified LasB impaired significantly the ability of AM to clear an unrelated bacterium, namely S. pneumoniae. These data provide a new mechanism of action for LasB, potentially partly explaining the early onset of Pseudomonas aeruginosa, alone, or with other bacteria, within the alveolar lumen in susceptible individuals, such as ventilated, COPD and cystic fibrosis patients.